1987
DOI: 10.1111/j.1600-079x.1987.tb00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Both Hydroxy‐and Methoxyindoles Modify Basal Temperature in the Rat

Abstract: The various pineal gland tryptophan metabolites were administered to male rats intraperitoneally (100 micrograms/kg) and rectal temperatures were recorded. Of the compounds tested, hydroxytryptophan, N-acetylserotonin, hydroxytryptophol, and their corresponding methoxyindoles all caused a marked hypothermia, indicating that several indolic products may be involved in thermoregulation. Although the brain penetration of indoles is poor, a central site of action would be most likely, although peripheral actions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…During the process of oxidative stress injury, mitochondria are both a significant source of ROS and also a target of damage, with a variety of consequences. Based on the prominent role of mitochondria in oxidative stress injury, many studies have clearly shown that ROS leads to cell apoptosis via the mitochondria-dependent apoptotic pathway, which involves damage to the mitochondrial membrane, release of Cyt-C into the cytoplasm followed by caspase-3 activation, and finally hepatocyte apoptosis [30]. The morphologic changes in nuclei, the dissipation of ΔΨ m , the release of Cyt-C, and the expression of cleaved caspase-3 were employed as apoptotic biomarkers to elucidate the mechanisms underlying the antiapoptotic effects of NAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of oxidative stress injury, mitochondria are both a significant source of ROS and also a target of damage, with a variety of consequences. Based on the prominent role of mitochondria in oxidative stress injury, many studies have clearly shown that ROS leads to cell apoptosis via the mitochondria-dependent apoptotic pathway, which involves damage to the mitochondrial membrane, release of Cyt-C into the cytoplasm followed by caspase-3 activation, and finally hepatocyte apoptosis [30]. The morphologic changes in nuclei, the dissipation of ΔΨ m , the release of Cyt-C, and the expression of cleaved caspase-3 were employed as apoptotic biomarkers to elucidate the mechanisms underlying the antiapoptotic effects of NAS.…”
Section: Discussionmentioning
confidence: 99%
“…NAS, the immediate precursor of melatonin in the tryptophan metabolic pathway in the pineal gland, is a free radical scavenger. NAS has recently been shown to have various biologic activities, including memory-facilitating [29], hypothermic [30], analgesic [31], circadian rhythm adjustment [32], antidepressant [32], antiaging [33], lowering blood pressure [28], and antioxidative effects [28]. As described in our recent reports, NAS protects against acute hepatic I/R injury in mice by reversing the imbalance between oxidants and antioxidants and inhibiting hepatocyte apoptosis via the intrinsic apoptotic pathway [34] and offers neuroprotection through inhibiting mitochondrial death pathways in experimental models of ischemic stroke [35].…”
Section: Introductionmentioning
confidence: 99%
“…5-Methoxytryptophol displays a property otherwise known from melatonin (1) and N-acetylserotonin (2), the ability to decrease body temperature. The indole alcohol was even reported to be more efficient in this regard than the pineal hormone [260]. In another metabolic step, 5-methoxytryptophol is transformed to O-acetyl-5-methoxytryptophol, a melatonin homolog also found in the pineal gland [37].…”
Section: Melatonin Metabolism In the Central Nervous Systemmentioning
confidence: 98%
“…The data available indicate varied results [6]. While there are some reports suggesting a hyperthermic ac tion [8,9], there are others suggesting a hypo thermic action [10,11] of melatonin. Heldmaier et al [12] indicated that photoperiodic information which may be important in cue ing thermoregulatory adjustments is pro cessed in much the same manner as the photoperiodic information that is important in con trolling gonadal activity.…”
Section: Introductionmentioning
confidence: 99%